(untitled) (Research, Society and Development, 2022)
Introduction: Charcot-Marie-Tooth disease (CMT) is the most prevalent genetically determined neurological condition in the world, individuals have muscle weakness, atrophy and sensory deficit. Objective: Assess lower limb and trunk muscle strength in individuals with CMT type 2 and its correlations with balance and functionality. Methods: Cross-sectional study, with a sample of fifteen individuals in the CMT2 group (CMT2G) and fifteen in the control group (CG). To assess muscle strong (MS), the dynamometer was used; balance through stabilometry (Velocity of the Center of Pressure Oscillation (VCPo) anteroposterior (AP) and latero-lateral (LL); and the Berg Balance Scale (BSE); and for functional performance, the Time Up and Go (TUG). Results: There was a significant reduction in proximal MS of lower limbs, abdominal and paravertebral; lower BSE score and lower TUG of CMT2G compared to CG. When analyzing the correlations of LL and trunk strength with VCPoAP in CMT2G (individuals with a mild score), the muscles with the highest correlation were: hip and paravertebral extensors/abductors/adductors, while in moderate/severe individuals, there was a regular correlation with hip and paravertebral flexors. In the correlations with BSE (light score), the paravertebral muscles had a regular correlation and in the most affected there was a strong correlation with the hip extensors/flexors/abductors and regular with the abdominals. In the correlations with the TUG (light score), there was a regular correlation with the hip, abdominal and paravertebral flexors. In moderate/severe individuals, the hip and paravertebral flexors had a slight correlation.